ANTARA BIOGRAFI DAN HISTORIOGRAFI (Studi 36 Buku Biografi di Indonesia ) - Daud, Safari (Universitas Islam Negeri Raden Intan Lampung, 2013)
The writing of the religious leaders in Indonesia ranks the second after political figures ones. This ranking is the result of Gerry van Klinken’ research on biographies writings in Indonesia from1950 to 2000 as many as 2,629 books . As the domain of science history , the quantity of writing biographies have not shown the quality of historiography. A total of 36 biography books that the writer analyzed using prevalence history method found out four historiographical issues. First, in the writing of character’s biography about his life has an impact on a critical attitude gap between academic interests of biographer and psychological pressure from mainstream figures who has written. Second, there is a plurality of the biographer rated from reporter, historians, scholars and experts from various professions with their own characteristics of literacy. Third, a biography written by historian is more scientific which shows the portion of the balance in the selection of figures, while the non- historian biographer is more interested in contemporary issues and prefer well-known figures. A variety of professions of the biographer is one of a consequences of the biography writing that much or even related to historiography.